The Gathering of Scattered Israel: The Missional Enterprise of The Church of Jesus Christ of Latter-day Saints - Bartholomew, Ronald E. (International bulletin of mission research, 2022)
This article focuses on LDS missionary theology; changing missionary practices, training, and demographics of the missionary force in historical perspective; the relationship between the size of the missionary force and church growth; and the LDS Church’s geographic expansion as an international church.